2020
DOI: 10.5507/bp.2020.042
|View full text |Cite
|
Sign up to set email alerts
|

Use of high-density EEG in patients with Parkinson's disease treated with deep brain stimulation

Abstract: The number of reports on cognitive changes related to deep brain stimulation (DBS) surgery in Parkinson's disease (PD) is growing. The aim of the review was to assess whether high-density electroencephalography (HD EEG) in patients with DBS treatment for PD is used and mentioned as a research method for the assessment of cognitive function changes after DBS of the subthalamic nucleus. The HD EEG examination method demonstrates the effects of DBS on changes of connectivity among various areas of the brain using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Our results further demonstrate that a standard 21‐channel EEG probably suffices to predict cognitive decline after STN DBS. Further insight into pathophysiological alterations underlying cognitive decline may be provided through source localization to more closely pinpoint anatomical substrates, 50,51 especially when combined with high‐density EEG setups or pre−post EEG settings 52 . However, these setups are less applicable in a clinical prediction setting which would have limited its current utility.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further demonstrate that a standard 21‐channel EEG probably suffices to predict cognitive decline after STN DBS. Further insight into pathophysiological alterations underlying cognitive decline may be provided through source localization to more closely pinpoint anatomical substrates, 50,51 especially when combined with high‐density EEG setups or pre−post EEG settings 52 . However, these setups are less applicable in a clinical prediction setting which would have limited its current utility.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical signals are recorded through noninvasive scalp electroencephalography (EEG) [116] or through invasive subdural electrocorticography (ECoG), which requires an implanted grid with contacts [117]. However, disturbance of the scalp makes the stability and consistency of EEG unable to fit the sufficiency requirement of input signal [118]. Thus, ECoG oscillations instead of EEG are utilized as input cortical signals of aDBS for PD [118,119].…”
Section: Cortical Signalsmentioning
confidence: 99%
“…However, disturbance of the scalp makes the stability and consistency of EEG unable to fit the sufficiency requirement of input signal [118]. Thus, ECoG oscillations instead of EEG are utilized as input cortical signals of aDBS for PD [118,119]. ECoG studies on PD patients revealed that high beta (20-30 Hz) power and gamma power are increased in M1 during movement tasks [120].…”
Section: Cortical Signalsmentioning
confidence: 99%